2016
DOI: 10.1080/15412555.2016.1249790
|View full text |Cite
|
Sign up to set email alerts
|

MMP-8, MMP-9 and Neutrophil Elastase in Peripheral Blood and Exhaled Breath Condensate in COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is characterised by progressive and irreversible airflow limitation associated with chronic inflammation involving cytokines and metalloproteinases (MMPs). MMP-8, MMP-9 and neutrophil elastase (NE) are known to be implicated in COPD but the factors influencing activation and suppression remain unclear. This study aimed to compare MMP-8, MMP-9 and NE in the peripheral blood of COPD patients and controls and to likewise assess exhaled breath condensate (EBC) for these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…Reportedly, juvenile MMP8‐deficient mice exhibited increased mortality, which seemed to result from reduced bacterial clearance due to reduced phagocytosis and diminished NET efficiency . MMP8 is also known to play an important role in the transport of leucocytes in chronic and acute inflammation; for example, increased expression of MMP8 is detected in the PBMCs of COPD patients with acute exacerbation (AECOPD) . Recent studies have shown that the expression of MMP8 is upregulated in the blood of patients with sepsis through transcriptomic analysis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reportedly, juvenile MMP8‐deficient mice exhibited increased mortality, which seemed to result from reduced bacterial clearance due to reduced phagocytosis and diminished NET efficiency . MMP8 is also known to play an important role in the transport of leucocytes in chronic and acute inflammation; for example, increased expression of MMP8 is detected in the PBMCs of COPD patients with acute exacerbation (AECOPD) . Recent studies have shown that the expression of MMP8 is upregulated in the blood of patients with sepsis through transcriptomic analysis .…”
Section: Discussionmentioning
confidence: 99%
“…30 MMP8 is also known to play an important role in the transport of leucocytes in chronic and acute inflammation; for example, increased expression of MMP8 is detected in the PBMCs of COPD patients with acute exacerbation (AECOPD). 31 Recent studies have shown that the expression of MMP8 is upregulated in the blood of patients with sepsis through transcriptomic analysis. 32 In the present study, we found that the expression of MMP8 in PBMCs in the early stage of sepsis was significantly higher than that in non-septic ICU patients and increased even further in patients with a septic shock.…”
Section: F I G U R E 8 Five Proteins From the Intersection: Non-septimentioning
confidence: 99%
“…Microbial overload in the airways could also induce the release of myeloperoxidase from neutrophils, generate cell debris and reactive oxygen species (ROS), and aggravate damage to pulmonary structures. 56,57 In response to DAMPs, PRRs such as TLRs on neutrophils in peripheral blood and lung tissue are also over-expressed, thereby amplify neutrophil recruitment and activation. 36,58 Excessive infiltration of neutrophils in the lungs leads to the release of MMPs and neutrophil elastase (stored in azurophilic granules), which mediate a protease-antiprotease imbalance in the lung.…”
Section: Neutrophilsmentioning
confidence: 99%
“…Of the 2 studies on MMP -9 in EBC from patients with COPD, one showed no correlation between MMP -9 and spirometry parameters (either in stable disease or exacerbation), 8 while in the other, such an analysis could not have been performed because MMP--9 was not found in EBC from any of the study participants. 20 We found lower total MMP -9 concentrations in patients with COPD who were treated with ICS when compared to those who were steroid -naive. Such a difference was not documented when active MMP -9 was compared; moreover, there was DISCUSSION Our study is one of the very few reports on MMP -9 concentrations in EBC in patients with COPD.…”
Section: Matrix Metalloproteinase 9 Levels and Functional And Clinicamentioning
confidence: 62%